1999
DOI: 10.1099/0022-1317-80-2-425
|View full text |Cite
|
Sign up to set email alerts
|

Complementation of P37 (F13L gene) knock-out in vaccinia virus by a cell line expressing the gene constitutively.

Abstract: Vaccinia virus produces two different infectious forms, intracellular mature virus (IMV) and extracellular enveloped virus (EEV

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…In agreement with this idea, a recent report showed that retention of a significant fraction of the B5R protein in the endoplasmic reticulum does not affect the wrapping process but rather leads to a reduction in the amount of B5R incorporated into EEV (26). Several of the EEV-specific proteins have been expressed previously in transfected cells (7,19,38,40). In general, our results using the SFV expression system are in good agreement with these studies.…”
Section: Vol 74 2000 Expression Of Vaccinia Virus Eev Envelope Protsupporting
confidence: 92%
“…In agreement with this idea, a recent report showed that retention of a significant fraction of the B5R protein in the endoplasmic reticulum does not affect the wrapping process but rather leads to a reduction in the amount of B5R incorporated into EEV (26). Several of the EEV-specific proteins have been expressed previously in transfected cells (7,19,38,40). In general, our results using the SFV expression system are in good agreement with these studies.…”
Section: Vol 74 2000 Expression Of Vaccinia Virus Eev Envelope Protsupporting
confidence: 92%
“…Finally, the fusion protein F13-GFP showed perinuclear staining and diffuse cytoplasmic localization. The intracellular localization of these proteins was in general agreement to that previously reported (5,15,19,21,35), indicating that the tags used did not have a generalized effect on their distribution. From the above-described results, we concluded that these proteins, except GFP-tagged F12, showed at least some degree of accumulation in areas close to the nucleus (Fig.…”
supporting
confidence: 88%
“…In addition, several examples of modulation in the distribution of certain IEV envelope proteins have been reported. For instance, the distribution of F13 and its palmitylation are modified by infection (5). Also, the distribution of B5 is modified by coexpression of F13 (15), and the incorporation of A36 into IEV membranes has been shown to depend on the expression of A33 (45).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that F13L-deleted viruses are "severely attenuated" (25,26), although the details of those studies have not been presented. Nude and SCID mice were susceptible to intranasal VV-WR challenge even at doses as low as 100 pfu, but survived a F13L-KO challenge with 10 6 pfu and showed no evidence of disease during the 2-month monitoring period.…”
Section: Discussionmentioning
confidence: 99%